Reviews - Brad E. Lucas; Heidi Estrem; Yufeng Zhang; William FitzGerald (Journal of the Assembly for Expanded Perspectives on Learning, 2008)
Brad E. Lucas - Teaching Multi writing: Researching and Composing with Multiple Genres, Media, Disciplines, and Cultures Heidi Estrem - CoUege Writing and Beyond: A New Framework for University Writing Instruction Yufeng Zhang - Reading Chinese Fortune Cookie: The Making of Chinese American Rhetoric William FtizGerald - Geographies of Writing: Inhabiting Places and Encountering Difference